2017
DOI: 10.1111/jocs.13220
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following embolization in patients with cardiac myxoma

Abstract: Embolization of cardiac myxomas is more likely to occur in papillary-type tumors, that are smaller in size and in patients presenting with preoperative atrial fibrillation. However, the presence of embolization at the time of surgery does not increase operative morbidity or mortality or affect long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…[3][4][5][6] Systemic embolization occurs in approximately 30-40% of patients with cardiac myxoma. 7,8 As 75-80% of the tumors arise in the left atrium, approximately half of the embolic events may affect the central nervous system (CNS). 9 The neurological manifestation of cerebral embolization depends on whether embolic tumor cells remain intraluminal, leading to ischemic stroke, invade the vessel wall, resulting in intracranial aneurysms, or, in rare circumstances, transgress the vessel wall, leading to brain parenchymal seeding.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Systemic embolization occurs in approximately 30-40% of patients with cardiac myxoma. 7,8 As 75-80% of the tumors arise in the left atrium, approximately half of the embolic events may affect the central nervous system (CNS). 9 The neurological manifestation of cerebral embolization depends on whether embolic tumor cells remain intraluminal, leading to ischemic stroke, invade the vessel wall, resulting in intracranial aneurysms, or, in rare circumstances, transgress the vessel wall, leading to brain parenchymal seeding.…”
Section: Introductionmentioning
confidence: 99%
“…Emboli can also be composed of thrombotic material covered with tumor cells. 12,13 Myxomas with an irregular tumor surface, tumor location, are more frequently associated with production of emboli. 13,14 There is no consensus regarding whether or not tumor size is related to the likelihood of a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization rates of patients with both the right and left cardiac myxomas vary between 25.3% [8] and 43% [9]. Studies have shown that morphology of cardiac myxoma is the most predictive factor of embolic events.…”
Section: Discussionmentioning
confidence: 99%